Breadstick technology for women nutrition during preconception preparation, pregnancy and lactation periods - Ivanova N. G.; Volkonskaya A. A. (Vestnik MGTU)
During pregnancy, the female body experiences an increased need for essential substances. In the course of developing the technology of breadsticks, spinach puree (30 %), melange (15 %) and grated Parmesan cheese (8 %) have been added as sources of B vitamins, calcium and magnesium, which have a beneficial effect on the heart, blood vessels and nervous system of a pregnant woman. Whole-ground chickpea flour mixed with first-grade wheat flour in a ratio of 1 : 3 has been used as an additional source of protein. The addition of additional ingredients has given the developed products a distinct taste and aroma. Increased acidity has not had a negative effect on the organoleptic properties of the finished product. The increase in crumb moisture has been due to the addition of spinach puree, which makes it possible to increase the estimated yield of products by 3–5 %. The data of determining the nutritional value by the calculation method show that the consumption of 100 g of the developed bread sticks satisfies the daily requirement of a woman in the first trimester of pregnancy for protein (23 %), vitamin K (about 71.7 %), vitamin B2 (11.1 %), vitamin B6 (10.0 %), vitamin B12 (6.7 %), folates (28.0 %), calcium (13.4 %), magnesium (19.4 %). The bakery product Palochki-Vyruchalochki is recommended for the prevention and elimination of micronutrient deficiency in women during pregravid preparation, as well as during pregnancy and subsequent lactation.